Influence of limiting the number of ball touches on players` tactical behaviour and network properties during football small-sided games - Brito E Sousa, R.; Bredt, S. D. G. T.; Greco, P. J.; Clemente, F. M.; Teoldo, I.; Praça, G. M. (International Journal of Performance Analysis in Sport, 2019)
This study aimed to compare the frequencies of core tactical principles, the percentages of successful tactical principles, and the general network properties of football small-sided and conditioned games (SSCG) with and without the limitation of the number of ball touches. Thirty-six under-15 national level football players participated in this study and performed atotal of 15,067 tactical actions. They performed four SSCG bouts with 4 minutes of passive recovery between each bout, in two experimental conditions: free-play SSCG and two-touch SSCG. Tactical behaviour and performance were analysed using the System of Tactical Assessment in Soccer and the Social Network Analysis, was used to measure players` interactions. Results showed that two-touch SSCG increased the frequency of actions of width and length without the ball (p = 0.001), depth mobility (p = 0.029), concentration (p = 0.001), and defensive unity (p = 0.001). The two-touch format also increased defensive performance (p = 0.005), density (p = 0.001), and clustering coefficient (p = 0.007). Therefore, coaches should adopt the two-touch rule for increasing ball circulation or to reduce the tactical complexity of the task for the defending team.